1992
DOI: 10.1055/s-2007-1010505
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Stent Occlusion - A Problem Solved with Self-Expanding Metal Stents?

Abstract: The main limitation in the endoscopic palliation of malignant biliary obstruction is due to stent blockage. One of the factors thought to be of importance is the diameter of the endoprosthesis. In this paper, we report the results of a multicenter European study with a one cm diameter self-expanding metal stent (Wallstent) in 103 patients with malignant biliary obstruction. Insertion of the stent following guidewire positioning was successful in 97.1% of the patients without any cases of de novo cholangitis de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 0 publications
3
48
0
5
Order By: Relevance
“…Postoperative mortality and morbidity after open biliary bypass reportedly range from 5% to 20% [2]. Other studies have reported a mortality rate of 27%, a procedure-related morbidity rate of 13%, and a reintervention rate of 12% [1,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative mortality and morbidity after open biliary bypass reportedly range from 5% to 20% [2]. Other studies have reported a mortality rate of 27%, a procedure-related morbidity rate of 13%, and a reintervention rate of 12% [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…The main drawback to these methods is the substantial occlusion of these stents by tumor ingrowth [4]. Duodenal stenting is usually not considered an option for the treatment of severe duodenal obstruction in patients with invasive carcinoma of the pancreas [15].…”
mentioning
confidence: 99%
“…AlI three stent types have been shown to be effective in the relief of obstruction and re-establishing patency of the biliary 16 tree but they differ in several aspects including physical characteristics, price, and average duration ofpatency [23][24][25].…”
Section: Research Problems and Objectivesmentioning
confidence: 99%
“…The problems associated with PE stent dysfunction were' at least partially overcome with the advent of U-SEMS. Once fully deployed, U-SEMS reaches an internaI diameter approximately 3 times bigger than PE stents, and is less likely to be c10gged by bile plugs and biofilm [23]. Instead, U-SEMS are rather obstructed by tumor ingrowth and outgrowth which occurs on average 8-9 months after placement [35][36][37].…”
Section: Research Problems and Objectivesmentioning
confidence: 99%
“…Quando estas opções não são possíveis, a drenagem do sistema biliar com cateteres biliares externos ou próteses internas são úteis para melhorar os sintomas, porém são passíveis de obstrução. A utilização de próteses expansíveis diminuiu esta incidência 10,11 . 16 .…”
Section: Opções Terapêuticasunclassified